ANALISIS STRUKTUR PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN ANTAR KABUPATEN/KOTA DI PROVINSI RIAU - Nazwar Akbar; Hamidi Wahyu; Kornita Endang Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study is to analyze the amount of inequality between regions and economic growth in the Province Of Riau based on the rate of growth and per capita income. The type of data used in this research is secondary data obtained from Badan Pusat Statistik (BPS). The analytical method used is the Location Quotient (LQ) analysis, Klassen typology, Williamson index, and Theil Entropy index. The results of the study using Location Quotient (LQ) analysis show that the districts of Kuantan Singingi, Indragiri Hilir, and Rokan Hulu are based on the agricultural sector. The districts of Kampar, Bengkalis, and Rokan Hilir are based on the mining sector. The districts of Pelalawan, Siak, and Dumai city are based on the manufacturing sector. Indragiri Hulu district is based on the water supply sector, the Meranti Island are based on the transportation sector, and Pekanbaru city is based on the financial services sector. Based on Klassen typology analysis, its explained that there are still areas in Riau Province which are classified as relatively underdeveloped areas, namely Kampar regency, Indragiri Hulu regency, and Rokan Hilir Regency. Inequality of income between regions in Riau Province in 2015-2019 is classified as moderate inequality and has a downward trend.Keywords : Income inequality, Economic Growth, Base Sector.